Assessing the uptake kinetics and internalization mechanisms of cell-penetrating peptides using a quenched fluorescence assay. - Mäger, I; Eiríksdóttir, E; Langel, K; Andaloussi, S; Langel, U (2010)
Cell-penetrating peptides (CPPs) have shown great potency for cargo delivery both in vitro and in vivo. Different biologically relevant molecules need to be delivered into appropriate cellular compartments in order to be active, for instance certain drugs/molecules, e.g. antisense oligonucleotides, peptides, and cytotoxic agents require delivery into the cytoplasm. Assessing uptake mechanisms of CPPs can help to develop novel and more potent cellular delivery vectors, especially in cases when reaching a specific intracellular target requires involvement of a specific internalization pathway. Here we measure the overall uptake kinetics, with emphasis on cytoplasmic delivery, of three cell-penetrating peptides M918, TP10 and pVec using a quenched fluorescence assay. We show that both the uptake levels and kinetic constants depend on the endocytosis inhibitors used in the experiments. In addition, in some cases only the internalization rate is affected by the endocytosis inhibitors while the total uptake level is not and vice versa, which emphasizes importance of kinetic studies when assessing the uptake mechanisms of CPPs. Also, there seems to be a correlation between lower total cellular uptake and higher first-order rate constants. Furthermore, this may indicate simultaneous involvement of different endocytic pathways with different efficacies in the internalization process, as hypothesized but not shown earlier in an uptake kinetics assay.